2014
DOI: 10.1002/cjce.21947
|View full text |Cite
|
Sign up to set email alerts
|

PDMS coated asymmetric PES membrane for natural gas sweetening: Effect of preparation and operating parameters on performance

Abstract: The present study is an attempt to investigate the effects of preparation and operation parameters on ideal and real selectivity of polydimethylsiloxane (PDMS) coated asymmetric polyethersulfone (PES) membranes for natural gas sweetening. Scanning electron microscopy (SEM) was used to study the effect of PES concentration and solvent type on membrane morphology. The effects of operating parameters on the performance of membranes were investigated by using binary CO 2 /CH 4 , H 2 S/CH 4 and ternary H 2 S/CO 2 /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 93 publications
(111 reference statements)
2
16
0
Order By: Relevance
“…The CO 2 permeability increased by increasing the feed pressure; however, the permeability of other gases decreased. The rubbery nature of the PUU and its polar ethereal groups are responsible for the enhancement of the CO 2 permeability with pressure . The enhancement is greater for the PUU–HDC–2.5 due to the high affinity of the particles toward CO 2 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The CO 2 permeability increased by increasing the feed pressure; however, the permeability of other gases decreased. The rubbery nature of the PUU and its polar ethereal groups are responsible for the enhancement of the CO 2 permeability with pressure . The enhancement is greater for the PUU–HDC–2.5 due to the high affinity of the particles toward CO 2 .…”
Section: Resultsmentioning
confidence: 83%
“…The rubbery nature of the PUU and its polar ethereal groups are responsible for the enhancement of the CO 2 permeability with pressure. 72 The enhancement is greater for the PUU-HDC-2.5 due to the high affinity of the particles toward CO 2 . The tendency of particles to interact more with CO 2 rather than other gases was shown in the recent publication.…”
Section: Gas Transport Propertiesmentioning
confidence: 97%
“…The separation efficiency of the SMM processes ( Fig. 1b) will also be reduced because of the low LHC/CO 2 selectivity of vapor membrane (Saedi et al, 2014;Scholes et al, 2012). As a result, the rectification operating cost has to be raised to maintain the quality of the LHC product (O'Donoughue et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…[9] Many composite polymeric membranes had been reported in the literature for gas separation applications. Saedi et al [14] developed a PDMS/PES composite membrane and reported the CO 2 /CH 4 real selectivity of 26.54. Similarly, Madaeni et al [11] developed a PDMS/PES (polyethersulphone) composite membrane with dip coating and manual film casting, and tested the developed membrane for CO 2 /N 2 and CO 2 /CH 4 separation.…”
Section: Introductionmentioning
confidence: 99%